2021
DOI: 10.3389/fpsyt.2021.649737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cognitive Remediation on Cognition, Metacognition, and Social Cognition in Patients With Schizophrenia

Abstract: We aimed to evaluate in a sample of outpatients with schizophrenia (SCZ) the effectiveness of a cognitive remediation (CR) program (through the use of the Cogpack software) [computer-assisted CR (CACR)] in addition to standard therapy on cognitive outcomes as compared with that in a control active group (CAG) and to highlight a possible effect on social cognition (SC), metacognition, symptomatology, and real-world functioning. Of the 66 subjects enrolled, 33 were allocated to CACR and 33 to the CAG. Twenty-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In addition, Garrido and Linke found that CCRT can improve the attention, memory, executive function and other cognitive fields of SCZ patients ( 26 , 27 ). CCRT improves working memory, attention and executive function and problem-solving abilities of patients with SCZ and thus improve the ability to recall the past and imagine the future ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Garrido and Linke found that CCRT can improve the attention, memory, executive function and other cognitive fields of SCZ patients ( 26 , 27 ). CCRT improves working memory, attention and executive function and problem-solving abilities of patients with SCZ and thus improve the ability to recall the past and imagine the future ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among others, cognitive remediation programs (CR) and physical activity are psychiatric and neurological rehabilitation interventions that showed to be effective in improving cognition, as the main outcome [ 6 , 21 , 22 , 23 , 24 ], as well as improving social and personal functioning outcome [ 25 , 26 , 27 ]. At the same time, physical activity and CR were proven to be effective to prevent cognitive decline in healthy populations [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with the very low rates of recovery found in individuals treated for a FEP when recovery is defined not only in terms of psychotic episodes but, more generally, as social and clinical recovery lasting for at least 2 years (together with mild symptoms): the percentage of patients found to meet these criteria in a meta-analysis of outcome studies reach just to 13.5% ( 3 , 5 ). Therefore, and with such a definition for recovery in mind, many researchers focused recently in the social functioning and the real-world adjustment of the patient ( 6 ) to determine the factors that can afford protection as well as those that represent an improved prognosis in the patient’s social life, with a large number of studies on both aspects (protection and prognosis) having been published since the beginning of this century ( 2 ). One of the main factors explored is cognition, since cognitive deficits represent one of schizophrenia’s core features, which affect patients’ functioning and recovery, and seems to be related to high levels of functional disability, even more so than psychopathology ( 7 ), what has led recently to a “white paper” of recommendations for good practitioners in therapy and rehabilitation for FEP patients, developed by experts in cognitive remediation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%